PENGARUH LATIHAN TEMBAKAN KE GAWANG INSTEP DRIVE TERHADAP KEMAMPUAN SHOOTING PADA TIM SEPAK BOLA TALENTA FC KOTA DUMAI - Putra, Tomy Dwi; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : The purpose of this research is to know the effect of exercise shots on goal instep the drive against the shooting on football team Talenta FC the city of Dumai. In this study researcher took population of the football team Talenta FC the city of dumai, amounting to 16 people. The researcher used the total sampling technique of saturated sample where all population sampled. The design of this study used one group pretest-posttest approach. The instrument was done measure the ability of the shooting by shots on target to the wall. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05). This hypothesis put forward influence of the shots on goal instep drive against the shooting. Based on statistical data analysis, it yields pretest data Lcount 0,1796, data posttest Lcount 0,2022 and Ltabel 0,213, mean Lcount < Ltabel. Then the data is normally distributed. Based on t test analysis yielded Tcount equal to 7 and Ttabel 1,75, mean Tcount> Ttabel .Thus, there is the influence of training shot on goal agaist the shootinf on the football team Talenta FC the city of Dumai.The Key Word: Shots on goal (Instep Drive), The Shooting